2016
DOI: 10.1097/mpg.0000000000000963
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related Quality of Life in Spanish Children With Coeliac Disease

Abstract: The CDDUX questionnaire emerged as reliable for use in Spanish children with celiac disease. Overall, both children and parents felt the disease had no substantial negative impacts on patient HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 41 publications
4
48
0
1
Order By: Relevance
“…In our study, children and adolscents with celiac disease and their parents gave similar answers in the pediatric questionnaire about quality of life (PedsQL), so all observed scores statistically were homogeneous. Our results are consistent with the results of European studies in which the evaluation of self-assessment of the quality of life of children and adolescents with celiac disease and assessment of their parents shows that the disease does not have significant negative impact on quality of life [16]. Unlike our results, other studies have found that parents have significantly poorer perception of health related quality of life of their children than the children themselves [15,17].…”
Section: Resultssupporting
confidence: 92%
“…In our study, children and adolscents with celiac disease and their parents gave similar answers in the pediatric questionnaire about quality of life (PedsQL), so all observed scores statistically were homogeneous. Our results are consistent with the results of European studies in which the evaluation of self-assessment of the quality of life of children and adolescents with celiac disease and assessment of their parents shows that the disease does not have significant negative impact on quality of life [16]. Unlike our results, other studies have found that parents have significantly poorer perception of health related quality of life of their children than the children themselves [15,17].…”
Section: Resultssupporting
confidence: 92%
“…Children and adolescents with CD aged two to 18 years old and/or their parents participated in the studies. In 14 of the 23 articles children and/or adolescents and their parents participated [ 13 , 16 , 18 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], in seven studies children and/or adolescents participated [ 35 , 36 , 37 , 38 , 39 ], and in one article only parents participated [ 40 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 23 articles included five main objectives, as follows: (1) Twelve articles involved assessment of QOL [ 13 , 16 , 19 , 26 , 29 , 31 , 32 , 33 , 35 , 36 , 37 , 42 ]; (2) Seven articles were associated with adherence to the GFD [ 28 , 35 , 36 , 39 , 41 ]; (3) Six articles were associated with the impact of a GFD on daily life [ 18 , 27 , 33 , 38 , 43 ]; (4) Five of the 23 articles were related to the impact of CD on the family or parents [ 25 , 29 , 38 , 39 , 40 ]; and (5) Five of the articles explored the relationships of QOL and adherence [ 13 , 28 , 35 , 36 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations